Barangay Volunteer Fire Brigade Program in Quezon, Palawan - Labaria, Alton (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed the implementation of the Barangay Volunteer Fire Brigade Program in Quezon, Palawan, with emphasis on the participants’ demographic profile, their perceptions of program implementation, the problems encountered, and the relationships among these variables. The study focused on three groups of participants: community members, Bureau of Fire Protection uniformed personnel, and barangay volunteer firefighters. Findings showed that many participants had direct involvement in volunteer firefighting, with an average length of service of 9.61 years, and several had attended relevant training related to fire prevention and emergency response. The assessment revealed varied perceptions among the participant groups. Community members perceived the program as fairly implemented in terms of organization and personnel, but poorly implemented in training and capabilities, practice drills, facilities, and equipment or apparatus. Bureau of Fire Protection personnel rated the program as fairly implemented across the assessed areas, while barangay volunteer firefighters viewed organization and personnel as very much implemented, training and capabilities as fairly implemented, and practice drills, facilities, and equipment or apparatus as poorly implemented. Significant relationships were found between selected participant profiles and their assessment of program implementation, as well as between participant profiles and the problems encountered. Factors such as sex, occupation, employment status, place of residence, fire victim status, highest educational attainment, and training attended influenced participants’ perceptions and experiences. Based on the findings, a proposed program was formulated to strengthen the organization, training, capabilities, facilities, equipment, and overall implementation of barangay volunteer fire brigades in Quezon, Palawan.
Keywords: Barangay Volunteer Fire Brigade, Fire Brigade Program, Program Implementation, Training and Capabilities, Firefighting Equipment and Apparatus